Используя метод введения новой переменной,решите уравнение: (1-x^2)^2+3,7(1-x^2)+2,1=0

0 голосов
60 просмотров

Используя метод введения новой переменной,решите уравнение: (1-x^2)^2+3,7(1-x^2)+2,1=0


Алгебра (303 баллов) | 60 просмотров
Дан 1 ответ
0 голосов

(1 - x²)² + 3,7(1 - x²) + 2,1 = 0
Обозначим: (1 - х²) = t, тогда
t² + 3,7t + 2,1 = 0
D= 13,69 - 8,4 = 5,29
t₁= (-3,7+2,3)/2 = -0,7
t₂= (-3,7-2,3)/2 = -3

1 - x² = -0,7
x²= 1,7
x₁,₂= +- √1,7

1 - x² = -3
x²=4
x₃,₄= +-2
Ответ: +-√1,7; +-2.

(33.3k баллов)